Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen Pada Hypermart Nagoya Hill Batam - Hisyam, Magneta (Tractare: Jurnal Ekonomi-Manajemen, 2022)
The study aims to look at how much influence products, prices, promotions, and venues have on consumer purchasing decisions on Hypermart Nagoya Hill Batam. This research was conducted with a survey approach. To prove the influence of the marketing mix on the consumer purchase decision of Hypermart Nagoya Hill Batam, the authors collected data by way of the dissemination of questionnaires, namely as many as 100 respondents as samples taken from all Consumers of Hypermart Nagoya Hill Batam. Data collected through questionnaires is processed using spss program applications.Based on the results of the study showed that the results of the F Test (Simultaneous) showed that the variables of the product, price, promotion, and place together had a positive and significant effect on consumer purchasing decisions at Hypermart Nagoya Hill Batam. The results of partial regression analysis (T Test) show that product variables have a positive and significant influence on purchasing decisions, price variables do not have a positive and significant influence on purchasing decisions; that promotional variables have a positive and significant influence on purchasing decisions; and place variables have a positive and significant influence on the purchasing decisions of consumers shopping at Hypermart Nagoya Hill Batam